GLOBAL AND RUSSIAN IPO MARKETS: KEY TRENDS AND OUTLOOK - B. B. Rubtsov (Real Economics Publishing House, 2014)
Global IPO markets achieved historical maximum in volumes in 2007 but as a result of the global financial crisis of 2008–2009 issuing activities substantially plummeted. However by the middle of 2009 capital markets began to revive. The paper provides the analysis of global IPO market trends and author’s view on the middle-term trends.